2019
DOI: 10.1111/codi.14471
|View full text |Cite
|
Sign up to set email alerts
|

Primary vs myocutaneous flap closure of perineal defects following abdominoperineal resection for colorectal disease: a systematic review and meta‐analysis

Abstract: Aim Perineal wound complications after abdominoperineal resection (APR) have become a major clinical challenge. Myocutaneous flap closure has been proposed in place of primary closure to improve wound healing. We conducted this comprehensive meta‐analysis to evaluate the current scientific evidence of primary closure vs myocutaneous flap closure of perineal defects following APR for colorectal disease. Methods We systematically searched the MEDLINE, Embase, PubMed, Web of Science and Cochrane Library databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…This multicenter case series suggests that minimally invasive TpAPE is feasible with acceptable intraoperative complications, no short-term mortality and a 9% severe postoperative complication rate within 30 days. The postoperative major morbidity rate of 9% compares favorably to major morbidity rates between 10 and 30% and perineal wound infection ranging from 11 up to 50% reported in large series and meta-analysis, but the current study is limited by the small sample size and inherent case selection bias [21][22][23][24][25][26]. Five intraoperative complications were reported, four of which were related to wrong plane surgery with sequential perforation, urethral, and pelvic sidewall injury.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This multicenter case series suggests that minimally invasive TpAPE is feasible with acceptable intraoperative complications, no short-term mortality and a 9% severe postoperative complication rate within 30 days. The postoperative major morbidity rate of 9% compares favorably to major morbidity rates between 10 and 30% and perineal wound infection ranging from 11 up to 50% reported in large series and meta-analysis, but the current study is limited by the small sample size and inherent case selection bias [21][22][23][24][25][26]. Five intraoperative complications were reported, four of which were related to wrong plane surgery with sequential perforation, urethral, and pelvic sidewall injury.…”
Section: Discussionmentioning
confidence: 60%
“…The wider and thereby more radical excision comes at the cost of a larger defect of the pelvic floor and skin [17][18][19][20]. Previous studies and meta-analyses have reported major morbidity rates between 10-30% and perineal wound healing problems from 11 up to 50% [21][22][23][24][25][26]. Especially in irradiated patients, perineal wound healing is problematic and sometimes requires primary or secondary reconstruction with musculocutaneous flaps to achieve perineal closure [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of any beneficial effects of OP as found in the present meta-analysis is in contrast to literature on autologous tissue flaps for perineal wound closure following APR. 11,43 In particular, the use of a VRAM flap is well established. 8,30,44 However, studies directly comparing muscle flaps and OP are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Although VRAM flap closure has been effectively used in selective populations, 8 there remains the issue of donor and recipient site morbidity. 43,47 A smaller flap without donor site problems such as the perineal turnover flap 48 seems attractive. We are currently evaluating the effectiveness of a modified gluteal turnover flap 49 for routine use after APR, and we consider larger fascio-cutaneous gluteal or VRAM flaps only for the wider perineal defects with a high risk of sinus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Another significant advancement in the care of patients undergoing APE has been the use of musculocutaneous or fasciocutaneous flaps to close the perineal defect, particularly after the use of preoperative CRT 11,12 . A recent meta‐analysis of 18 studies including 17,913 patients demonstrated that the use of a perineal flap is associated with fewer wound complications and wound infections 13 . Compared to primary closure, flaps are associated with an increased wound healing rate and a reduced risk of developing a pelvic abscess 14 .…”
Section: Introductionmentioning
confidence: 99%